Habitat use of proboscis monkey (Nasalis larvatus) in production forests of West Kalimantan, Indonesia - WARDATUTTHOYYIBAH WARDATUTTHOYYIBAH; SATYAWAN PUDYATMOKO; MUHAMMAD ALI IMRON; SENA ADI SUBRATA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wardatutthoyyibah, Pudyatmoko S, Imron MA, Subrata SA. 2023. Habitat use of proboscis monkey (Nasalis larvatus) in production forests of West Kalimantan, Indonesia. Biodiversitas 24: 1724-1734. Proboscis monkeys (Nasalis larvatus van Wurmb 1787) are endemic to Borneo and dependent on the presence ofwetlandforest as their habitat. Recent study shows that many potential habitats of this species are in non-protected areas including logging concessions. We investigate the use of logging concessions for the habitat of proboscis monkeys by determining habitat variables that influence the presence of proboscis monkeys in a selective logging system. We conducted research in seven logged-over areas/LOA during 2009-2015 and eight locations of unlogged forest as proboscis monkey habitat. We applied a logistic regression with the backward stepwise method for selecting environmental variables that influence the presence of proboscis monkeys. Our study showed that proboscis monkeys are no longer present in LOAs, which was indicated by the difference between the habitat characteristics of proboscis monkeys and LOAs. We found that if prosboscis monkeys are presentin an area, resource selection was influenced at site level for basal area of trees and poles explained the presence of proboscis monkeys. Reducing the number of trees logged and ensuring connectivity among trees in LOAs could help to reestablish habitat for proboscis monkeys.